The Impact of Cognition on Radar Technology - Farina, A. 1948-; De Maio, Antonio (College teacher); Haykin, Simon S., 1931- (SciTech Publishing Inc., 2017)
The following topics are dealt with: cognitive radar; CFAR detection; receiver adaptation; cognitive optimization; transmitter-receiver pair; radar target tracking; MIMO radar; electronic warfare and synthetic aperture radar.
Keywords: Automatic tracking.; MIMO systems.; Radar.; Synthetic aperture radar.; Tracking radar.; elektronické knihy; electronic books